Peran Aplikasi Mobile dalam Meningkatkan Efisiensi dan Kualitas Layanan Jasa Kebersihan Modern - Jonathan; Agus Danarto (Indonesian Journal Publisher, 2025)
This study aims to analyze how mobile applications can improve User Experience (UX), E-Service Quality, Customer Satisfaction, and Customer Retention in the Pojok Bersih sanitation service. The methods used in this study are descriptive qualitative through interviews, service process observation, and user needs analysis. The target users were specified as young workers aged 25–35 years in the Pontianak City area. The results of the study show that digitizing services with features such as a simple interface, intuitive navigation, quick booking features, staff tracking, and price transparency can increase customer satisfaction and improve e-service quality. This improvement in service quality has a direct impact on high customer satisfaction levels, which in turn strengthens user retention for the Pojok Bersih service. All research findings support the hypothesis that UX has a positive effect on E-Service Quality, which increases Customer Satisfaction and strengthens Customer Retention. This study recommends the development of a Pojok Bersih mobile application with more responsive, clear, and secure features to meet the needs of people who require fast and practical cleaning services.